2007
DOI: 10.1002/rcm.2976
|View full text |Cite
|
Sign up to set email alerts
|

‘N‐in‐one’ strategy for metabolite identification using a liquid chromatography/hybrid triple quadrupole linear ion trap instrument using multiple dependent product ion scans triggered with full mass scan

Abstract: This paper describes a new strategy that utilizes the fast trap mode scan of the hybrid triple quadrupole linear ion trap (QqQ(LIT)) for the identification of drug metabolites. The strategy uses information-dependent acquisition (IDA) where the enhanced mass scan (EMS), the trap mode full scan, was used as the survey scan to trigger multiple dependent enhanced product ion scans (EPI), the trap mode product ion scans. The single data file collected with this approach not only includes full scan data (the survey… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Only one study has demonstrated so far, using a similar approach to that described herein, that the combination of the EMS survey and EPI-dependent scan modes could be applied to drug metabolite profiling [11]. Both this and the present methods took advantage of the so-called , dynamic background subtraction script' of Analyst software to improve the S/N and peak resolution and guarantee the detection of minor metabolites.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Only one study has demonstrated so far, using a similar approach to that described herein, that the combination of the EMS survey and EPI-dependent scan modes could be applied to drug metabolite profiling [11]. Both this and the present methods took advantage of the so-called , dynamic background subtraction script' of Analyst software to improve the S/N and peak resolution and guarantee the detection of minor metabolites.…”
Section: Discussionmentioning
confidence: 89%
“…In contrast to standard protein precipitation methods, it is suitable for both in vivo and in vitro biological samples with minor changes in the sample working procedure. It probably represents an important advantage as compared to the procedure used by Li et al [11], which consisted in protein precipitation followed by evaporation and reconstitution of the dried extracts in the mobile phase. As pointed out by the authors themselves, such a procedure may result in concentrating the interfering compounds (especially from complex matrices) and thus in an increased background noise which may prevent minor metabolites to trigger dependent scans.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…To evaluate species differences in the metabolite profile of AMI, metabolite identification was performed on the same samples used for the metabolic stability test by LC-QTRAP-MS operated in the information-dependent acquisition (IDA) mode [21,22]. Simultaneous collection of MS/MS spectra for identification, as well as semi-quantitative analysis of metabolites of AMI in liver microsomes of the four species, were achieved using predicted MRM (pMRM) transitions to cover the most common phase I and II as survey scans; the MRM transitions selected by the IDA criteria were then used to trigger the corresponding EPI scan.…”
Section: Simultaneous Determination Of Microsomal Metabolic Stabilitymentioning
confidence: 99%
“…Ming et al [11] recently combined multiple ion monitoring (MIM), MRM, enhanced mass scan (EMS) and EPI in the study of ritonavir metabolism. Li et al [12] also published a so-called "N in one" strategy for metabolite identification using a combination of EMS as survey scan and EPI as dependent scan. This strategy, similar to the General Unknown Screening procedure we formerly reported [13], was used for nefazodone, allowing the detection and characterization of unexpected metabolites.…”
Section: Introductionmentioning
confidence: 98%